Azaphilones and isocoumarin derivatives from Penicillum chermesinum FS625 isolated from the South China Sea. (8th June 2021) - Zhang, Jie; Chen, Yuchan; Liu, Zhaoming; Li, Saini; Zhong, Jinqian; Guo, Bohong; Liu, Hongxin; Zhang, Weimin
Graphical abstract: Highlights: Four new azaphilones were isolated from the fungus Penicillium chermesinum FS625. Azaphilones F and G were a pair of epimers sharing the same planar structure. Compounds 2–3, 5 and 7 showed moderate inhibitory activity toward NO production. Abstract: Five previously undescribed compounds, including four azaphilones chermesinones D-G (1 –4 ), one new isocoumarin derivative 6, 8-dihydroxy-3-methoxy-3, 7-dimethylisochroman-1-one (8 ), together with four known compounds were isolated from the marine-derived fungus Penicillium chermesinum FS625. Their structures were well established by comprehensive spectroscopic analysis. The absolute configurations of all the new compounds were successfully determined by the X-ray crystallography analysis or electronic circular dichroism (ECD) calculations, and confirmed by their biosynthetic pathways. Compounds 1 –9 were evaluated for in vitro cytotoxicity and anti-inflammatory activity. Compounds 2 –3, 5, and 7 showed weak inhibitory activity toward nitric oxide (NO) production in LPS-induced RAW 264.7 macrophages with IC50 values in the range of 69.65–95.84 µM.